National Wheat Day, Feb 13-14, 2023 - CGIAR (CGIAR System Organization, 2023)
This video playlist contains five videos from the National Wheat Day Workshop held last Feb. 13- 14, 2023.This event was organized in collaboration with the Academy of Scientific Research and Technology (ASRT). The event was funded by the United States Agency for International Development (USAID). This event is of part of the CGIAR Initiative on National Policies and Strategies (NPS) Egypt Seminar Series, organized by IFPRI, ICARDA, and other CGIAR Centers.